تأثير مواعيد حش الزعتر Thymus vulgaris L. في تركيب الأوراق وجودتها - عبد العزيز محمد; صارم سناء (Latakia University Journal -Biological Sciences Series, 2017)
نقد البحث خلال الموسمين 2010 – 2011 و 2011 – 2012 في قسم المحاصيل الحقلية بكلية الزراعة لدراسة تأثير مواعيد حش الزعتر على جودة الأوراق ونسبة الزيت العطري فيها، زرعت البذور في أصص بلاستيكية سعة 250غ تربة زراعية في 5/10/2010، وشتلت في موقع التجربة في منطقة الشيخ بدر,محافظة طرطوس(سورية) بتاريخ 1/2/2011 في ثلاثة مكررات صممت التجربة بالطريقة العشوائية الكاملة، ودرست ثلاثة مواعيد لحش الزعتر هي: 1ـ قبل الإزهار (T1) بعد 61 يوماً من التشتيل. 2ـ عند اكتمال الإزهار (T2) بعد 65 يوماً من التشتيل. 3ـ بعد انتهاء الإزهار «بداية العقد» (T3) بعد 72 يوماً من التشتيل. بينت الدراسة ما يلي: 1ـ أعطى موعد الحش قبل الإزهار (T1) زيادة معنوية في نسبة الرطوبة في العشب وزيادة معنوية في نسبة الكربوهيدرات، ونسبة الزيت الثابت في الأوراق مقارنة بموعدي الحش عند اكتمال الإزهار (T2) وبعد انتهاء الإزهار (T3). 2 ـ أعطى الحش عند اكتمال الإزهار (T2) زيادة معنوية في نسبة البروتين ونسبة الرماد ونسبة الزيت العطري في الأوراق مقارنة بموعدي الحش قبل الإزهار (T1) وبعد انتهاء الإزهار (T3). 3ـ سبب موعد الحش بعد انتهاء الإزهار (T3) انخفاض معنوي في نسبة الرطوبة في العشب ونسبة البروتين ونسبة الزيت الثابت في الأوراق مقارنة بموعدي الحش قبل الإزهار (T1) وعند اكتمال الإزهار (T2) بالمقابل أعطى موعد الحش بعد انتهاء الإزرها (T3) أعلى نسبة للألياف في أوراق الزعتر مقارنة بموعدي الحش (T1) و (T2) خلال موسمي البحث. The; research was carried out during the two agricultural seasons 2010/2011-2011/2012 at Par. of Agriculture, Department of crops, to study the effect of date harvesting of Thymus vulgaris L. on quantity and essential oil percentage thyme leaves . Planting seeds at 5/1/2010 at polyethylene don full 250/g soil and transplanting seedlings at 1/2/2011 experiment locationn in area Al-sheikh Bader,Tartous Governator(Syria) the experiment was randomized blocks designs. with three replications, using 3 harvesting dates Before flowering stage (T1) 61 days after transplanting. Full flowering stage (T2) ater 65 days after transplanting. After flowering stage "decennary binging" (T3) 72 days after transplanting. The results showed that: The harvesting time before flowring stage gave significant increasing in percentage of moisture of herb, significantly increasing carbohydrates, fat in leaves comparing to the another date harvesting full and after flowering stages (T1,T2) respectively. The harvesting of time full flowering (T2) gave significant increase at protein percentage, ash and essential oil in thyme leaves compared to the times harvesting before and after flowering stages (T1) and (T3) respectively. The harvesting time after flowering stages (T3) caused significantly decreased moisture percentage in herb, protein percentage and fat percentage in leaves compared to the two harvestings before and full flowering stages (T1) and (T2) on another hand significantly increased of total fiber compared to the (T1) and (T2) harvesting stages during the two seasons.